Dysregulated lncRNAs are Involved in the Progress of Sepsis by Constructing Regulatory Networks in Whole Blood Cells - Cheng, Yanwei; Cao, Xue; Zhang, Jiange; Chen, Dong; Zhu, Juan; Xu, Lijun; Qin, Lijie (Frontiers in Pharmacology, 2021)
Sepsis is a highly heterogeneous syndrome that is caused by an unbalanced host response to an infection. Long non-coding RNAs (lncRNAs) have been reported to exert regulatory roles in a variety of biological processes, and became potential biomarkers and therapeutic targets for diverse diseases. However current understanding on the roles of lncRNAs in sepsis are extremely limited. Herein, to decipher the underlying functions of lncRNAs, we re-explored the 83 transcriptome datasets from specimens with sepsis, no_sepsis by final diagnosis, and control. The results of differentially expressed genes (DEGs), differentially expressed lncRNAs (DElncRNAs) analysis and co-expression analysis of lncRNA-mRNA pairs were obtained. We found that the expression pattern of lncRNAs was significantly activated in sepsis specimens, with clearly distinguish in sepsis from no_sepsis and control specimens. By performing co-expression analysis, we found DElncRNAs were closely related to T cell activation and immune response related terms in sepsis by regulating mRNAs expression in trans manner. The lncRNA-mRNA network and qRT-PCR test revealed that lncRNAs LINC00861, RP11-284N8.3 and CTB-61M7.2 were significantly correlated with the pathogenesis of sepsis. In addition, weighted gene co-expression analysis (WGCNA) and cis-regulation analysis also revealed sepsis specific lncRNAs were highly associated with important biological processes correlated with sepsis. In summary, the systematic dysregulation of lncRNAs are tightly involved in the remodeling of gene expression regulatory network in sepsis, and the lncRNA-mRNA expression network may be used to refine biomarker predictions for developing novel therapeutic approaches in sepsis.